Hollywood's West : the American frontier in film, television, and history - O'Connor, John E.; Rollins, Peter C. (The University Press of Kentucky, 2005)
Hollywood's West examines popular perceptions of the frontier as a defining feature of American identity and history. Seventeen essays by prominent film scholars illuminate the allure of life on the edge of civilization and analyze how this region has been represented on big and small screens. Differing characterizations of the frontier in modern popular culture reveal numerous truths about American consciousness and provide insights into many classic Western films and television programs, from RKO's 1931 classic Cimarron to Turner Network Television's recent made-for-TV movies. Many of the films discussed here are considered among the greatest cinematic landmarks of all time.